An insight into new glycotherapeutics in glial inflammation: Understanding the role of glycosylation in mitochondrial function and acute to the chronic phases of inflammation. (15th November 2022) - Patil, Vaibhav; Bohara, Raghvendra; Winter, Carla; Kilcoyne, Michelle; McMahon, Siobhan; Pandit, Abhay
Abstract: Introduction: Glycosylation plays a critical role during inflammation and glial scar formation upon spinal cord injury (SCI) disease progression. Astrocytes and microglia are involved in this cascade to modulate the inflammation and tissue remodeling from acute to chronic phases. Therefore, understating the glycan changes in these glial cells is paramount. Method and results: A lectin microarray was undertaken using a cytokine‐driven inflammatory mixed glial culture model, revealing considerable differential glycosylation from the acute to the chronic phase in a cytokine‐combination generated inflamed MGC model. It was found that several N‐ and O‐linked glycans associated with glia during SCI were differentially regulated. Pearson's correlation hierarchical clustering showed that groups were separated into several clusters, illustrating the heterogenicity among the control, cytokine combination, and LPS treated groups and the day on which treatment was given. Control and LPS treatments were observed to be in dense clusters. This was further confirmed with lectin immunostaining in which GalNAc, GlcNAc, mannose, fucose and sialic acid‐binding residues were detected in astrocytes and microglia. However, the sialyltransferase inhibitor inhibited this modification (upregulation of the sialic acid expression), which indeed modulates the mitochondrial functions. Conclusions: The present study is the first functional investigation of glycosylation modulation in a mixed glial culture model, which elucidates the role of the glycome in neuroinflammation in progression and identified potential therapeutic targets for future glyco therapeutics in neuroinflammation. Abstract : Workflow describing steps involved in the lectin microarray to understand the glycosignature in the mixed culture model.